High pressure phase behavior modeling of asymmetric alkane + alkane binary systems with the RKPR EOS - Cismondi Duarte, Martín (2014)
Very asymmetric hydrocarbon mixtures present an interesting academic challenge for their modeling. In addition, they are becoming more important technologically, since the world oil reserves are becoming heavier in average. The RKPR EOS was developed in recent years in order to consider asymmetric systems and allow for a good representation of densities for different types of compounds while maintaining the relative simplicity of cubic equations of state. In this work the RKPR EOS is applied for the first time for the correlation of phase behavior in the series of binary systems methane + n-alkane and ethane + n-alkane. In addition to the use of attractive and repulsive interaction parameters with quadratic mixing rules, the role of the extra degree of freedom that the RKPR model offers for setting the pure compound parameters was also examined. A new table of RKPR pure compound parameters was defined for n-alkanes. A comparative study was made with the Peng–Robinson EOS, based on following the same optimization procedure for interaction parameters.